Investigation of the linear and mode-coupled flow harmonics in Au+Au collisions at sNN = 200 GeV - STAR Collaboration (Physics Letters B, 2020)
Flow harmonics (vn) of the Fourier expansion for the azimuthal distributions of hadrons are commonly employed to quantify the azimuthal anisotropy of particle production relative to the collision symmetry planes. While lower order Fourier coefficients (v2 and v3) are more directly related to the corresponding eccentricities of the initial state, the higher-order flow harmonics (vn>3) can be induced by a mode-coupled response to the lower-order anisotropies, in addition to a linear response to the same-order anisotropies. These higher-order flow harmonics and their linear and mode-coupled contributions can be used to more precisely constrain the initial conditions and the transport properties of the medium in theoretical models. The multiparticle azimuthal cumulant method is used to measure the linear and mode-coupled contributions in the higher-order anisotropic flow, the mode-coupled response coefficients, and the correlations of the event plane angles for charged particles as functions of centrality and transverse momentum in Au+Au collisions at nucleon-nucleon center-of-mass energy sNN= 200 GeV. The results are compared to similar LHC measurements as well as to several viscous hydrodynamic calculations with varying initial conditions.
10 citations (Crossref) [2023-10-31] tex.ids: adamInvestigationLinearModecoupled2020, adamInvestigationLinearModecoupled2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85090403270 type: Article
Keywords: Collectivity; Correlation; Shear viscosity; dept.phy; peer-reviewed